Notas a modo de introducción El área centroamericana: descripción geopolítica y literario–cultural - Moro, Diana (2019)
Use Central American literature or Central American literatures as a term of analysis in the literary-cultural field? The question is supported by this dossier, which presents part of the literary diversity that belongs to the region from the academic perspective of South, North and Central America, contributing to the vitality of the discussion in the Transareal Studies. This perspective has been nourished with the contributions of the XVI International Congress of Central American Literature (CILCA) and the III Central American Workshop on Digital Repositories, as well as the follow-up given by Istmo, Virtual Journal of Central American Literary and Cultural Studies, an effort to which the Ístmica Magazine has also added.